Identification and development of implementation strategies: the important role of codesign - van der Laag, Patricia J.; Dorhout, Berber G.; Heeren, Aaron A.; Veenhof, Cindy; Barten, Di-Janne J. A.; Schoonhoven, Lisette (Frontiers in Health Services, 2024)
described and take the implementation context insufficiently into account. To unravel the black box in implementation strategy development, insight is needed in effective theoretically founded and practically informed strategies. The current study aims to describe the stepwise development of a practical, and theory-informed implementation strategy bundle to implement ProMuscle, a nutrition and exercise intervention for community-dwelling older adults, in multiple settings in primary care. Methods: The first four steps of Implementation Mapping were adopted to develop appropriate implementation strategies. First, previously identified barriers for implementation were categorized into the constructs of the Consolidated Framework for Implementation Research (CFIR). Second, the CFIR-ERIC matching Tool linked barriers to existing implementation strategies. Behavioral change strategies were added from literature where necessary. Third, evidence for implementation strategies was sought. Fourth, in co-design with involved healthcare professionals and implementation experts, implementation strategies were operationalized to practical implementation activities following the guidance of Proctor et al (2013). These practical implementation activities were processed into an implementation toolbox, which can be tailored to a specific context, and presents prioritized implementation activities chronologically. Results: A previous study identified and categorized a total of 654 barriers for implementation of a combined lifestyle intervention to the CFIR framework. Subsequently, the barriers were linked to 40 strategies. As many strategies affected multiple barriers, seven overarching themes emerged based on the strategies: assessing the context, network internally, network externally, costs, knowledge, champions, patient needs and resources. Co-design sessions with professionals and implementation-experts resulted in supported and tangible implementation activities for the final 20 strategies. The implementation activities were processed into a web-based implementation toolbox and allows healthcare professionals to tailor the implementation activities to their specific context and facilitates healthcare professionals chronologically during their implementation process. Conclusion: A theory-informed approach in combination with co-design with stakeholders is a usable Implementation Strategy Mapping Method to develop a practical implementation strategy bundle to implement ProMuscle in multiple settings in primary care. Next step is to evaluate the developed implementation strategies including the implementation toolbox on the implementation and adoption of ProMuscle.